2019
DOI: 10.36505/exling-2012/05/0007/000213
|View full text |Cite
|
Sign up to set email alerts
|

Stress and syllable structure durations in Greek

Abstract: This is an experimental study of segmental durations as a function of lexical stress production and syllable structure in Greek. In accordance with a production experiment, the results indicate that lexical stress production has different effects on different syllable structure constituents. Thus, the vowels are lengthened more than prevocalic consonants whereas stress production has a shortening effect on postvocalic consonants. These results imply that vowels are the main carriers of stress distinctions in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
9

Year Published

2019
2019
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 1 publication
0
8
0
9
Order By: Relevance
“…vowel nucleus > onset consonant > coda consonant. On the other hand, the lengthening effect of lexical stress application on onset consonant and vowel nucleus as well as the absence of any lengthening effect of focus application on any syllable constituent have been corroborated (Botinis 1989, Fourakis, Botinis, Katsaiti 1999.…”
Section: Discussionmentioning
confidence: 86%
“…vowel nucleus > onset consonant > coda consonant. On the other hand, the lengthening effect of lexical stress application on onset consonant and vowel nucleus as well as the absence of any lengthening effect of focus application on any syllable constituent have been corroborated (Botinis 1989, Fourakis, Botinis, Katsaiti 1999.…”
Section: Discussionmentioning
confidence: 86%
“…Recent experimental studies have shown that stressed and unstressed vowels in Standard Modern Greek show consistent differences not only in amplitude, but also in duration. (Botinis, 1989, Arvaniti, 2000, Fourakis et al, 1999. Contrary to these results, Pernot (1907) found that in Chios Greek rising tone was more consistent correlate of stress than duration or amplitude.…”
Section: Introductionmentioning
confidence: 94%
“…Lexical stress production in statements may be associated with a tonal rise in prefocus position whereas, in focus position, a local tonal expansion is followed by a postfocus tonal flattening (e.g. Botinis 1989). In polar questions, on the other hand, there is no tonal expansion of focus asignment but a rise-falling shape at the right edge (e.g.…”
Section: Introductionmentioning
confidence: 99%